2009
DOI: 10.1159/000183897
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Activity of 11β-Hydroxysteroid Dehydrogenase Type 1 Enzyme in Subcutaneous and Visceral Adipose Tissue of Prepubertal Children

Abstract: Background: Glucocorticoid excess promotes visceral obesity and cardiovascular disease. Ligand availability to the glucocorticoid receptor is controlled by isoforms of 11β-hydroxysteroid dehydrogenase (11β-HSD) which converts endogenous cortisone to active cortisol. Aim: To evaluate the expression and activity of 11β-HSD1 in subcutaneous adipose tissue (SC) and visceral adipose tissue (VAT) in prepubertal children with normal weight. Methods: Fourteen patients (11 female/3 male) with a mean age of 6.9 ± 0.9 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 38 publications
3
12
0
Order By: Relevance
“…Superficial subcutaneous adipose tissue and visceral fat also present similar 11β-HSD1 mRNA levels, except in obese patients, who display higher 11β-HSD1 mRNA expression in subcutaneous adipose tissue (Goedecke et al, 2006). Increased 11β-HSD1 expression in visceral fat was also found in prepubertal children with normal birth weight and normal BMI despite the presence of similar GRα mRNA expression in subcutaneous and visceral adipose tissues (Mericq et al, 2009).…”
Section: Discussionmentioning
confidence: 83%
“…Superficial subcutaneous adipose tissue and visceral fat also present similar 11β-HSD1 mRNA levels, except in obese patients, who display higher 11β-HSD1 mRNA expression in subcutaneous adipose tissue (Goedecke et al, 2006). Increased 11β-HSD1 expression in visceral fat was also found in prepubertal children with normal birth weight and normal BMI despite the presence of similar GRα mRNA expression in subcutaneous and visceral adipose tissues (Mericq et al, 2009).…”
Section: Discussionmentioning
confidence: 83%
“…Polycystic ovary syndrome and obesity are independently associated with increased expression of 11βHSD1 [21]. Consistently, Mericq et al [22] demonstrated a positive correlation between mRNA expression of 11βHSD1 in VAT and BMI in children. However, others studies have failed to show this increase and this relationship [23,24].…”
Section: Introductionmentioning
confidence: 85%
“…Tomlinson et al [25] even showed that weight loss increases 11βHSD1 expression in human isolated adipocytes. Moreover, data regarding gene expression of 11 β HSD1 in VAT and SAT are also conflicting [22,23,24,26,27]. …”
Section: Introductionmentioning
confidence: 99%
“…32 With increasing obesity, adipose tissue displays markedly abnormal adipocyte hypertrophy and activity, including increased production of pro-inflammatory cytokines (for example, interleukin-6, interleukin-1b and tumor necrosis factor-a), fatty acids and intracellular cortisol, which may alter GHR expression. [33][34][35][36][37] Differences in GHR expression between omental and subcutaneous adipose depots We found in the present study that lean individuals express significantly higher levels of GHR mRNA in the omental vs subcutaneous adipose tissues. Many differences in the metabolic activities of the two depots have been documented, including adipocyte sensitivity to lipolytic signals other than GH, such as catecholamines.…”
Section: Indicators Of Gh Sensitivity In Obesitymentioning
confidence: 92%
“…This may be because of differences in the immediate micro-environment of these tissues during obesity. 35,37,38,40 In contrast, trGHR/GHR ratios have significant positive associations with obesity only in the subcutaneous depots, suggesting that dominantnegative effects may influence GH signalling in this depot.…”
Section: Indicators Of Gh Sensitivity In Obesitymentioning
confidence: 99%